Teaching Material on Metaverse For Motion Dynamics Subject For Students (Motion Dynamic Metaverse (Md-Verse) - Fretycia Laurenty; Winny Liliawati; Taufik Ramlan Ramalis; Irma Rahma Suwarna (Eduvest - Journal of Universal Studies, 2024)
The advancement of technology has brought significant impacts to the world of education, opening opportunities for the development of more engaging and innovative learning methods. The utilization of technology, especially in science education such as physics, enables the presentation of material in a visual, interactive, and concrete manner. One of the recent breakthroughs is the concept of Motion Dynamic Metaverse (MD-Verse), which adds a new dimension to physics learning through virtual environments. With its interactive features, MD-Verse provides a dynamic and enjoyable learning experience. This research aims to develop Metaverse Teaching Materials on the topic of dynamics of motion for college students. Validation results indicate that MD-Verse is suitable for use in physics teaching, contributing to enhancing students' understanding and interest in physics concepts.